Preference for and tolerance of the intensity of exercise: brazilian portuguese adaptation and validation, normative values, factors associated and relationship with exercise behavior - Smirmaul, Bruno De Paula Caraça [UNESP] (2016)
Affective responses during exercise are related to exercise adherence and current/future exercise behavior. However, there is large inter-individual variability in affective responses to exercise. Such variability is partly explained by individual differences in preference for and tolerance of the intensity of exercise. Thus, the aims of this PhD thesis were: Article 1 – to adapt the Preference for and Tolerance of the Intensity of Exercise Questionnaire (PRETIE-Q) for the Brazilian population and to perform an initial psychometric evaluation; Article 2 – to test the structural validity of the PRETIE-Q in a diverse population sample and to evaluate its factorial invariance across gender and age subgroups; Article 3 – to explore the factors associated with Preference for and Tolerance of the exercise intensity in a diverse population sample, as well as to provide population-based normative values; Article 4 – to test whether the constructs of preference for and tolerance of exercise intensity are associated to exercise behavior longitudinally in a diverse population sample. For this, the following methods were used: Article 1 – translation and back-translation, production of a Brazilian Portuguese version of the PRETIE-Q, and psychometric evaluation and construct validation using cross-sectional correlations between the Preference and Tolerance scores and physical activity variables; Article 2 – confirmatory factor analysis and a test of multigroup factor invariance of the Brazilian Portuguese version of the PRETIE-Q across gender and age subgroups in a population sample of 622 participants; Article 3 – multiple linear regression between Preference and Tolerance scores with age, gender, BMI and moderate and vigorous leisure-time physical activity (LTPA) in a population sample of 622 participants; Article 4 – multiple linear regressions, partial correlations and multinomial logistic regressions involving demographic and anthropometric variables, as well as exercise behavior from both 2007-2008 and 2014-2015 of 622 participants. The results were: Article 1 – The Brazilian Portuguese version of the PRETIE-Q retained the psychometric properties of the original, demonstrating adequate internal consistency, testretest reliability, and cross-sectional correlations with physical activity variables among young adults. Article 2 – The Brazilian Portuguese version of the PRETIE-Q retained the structural properties of the original and demonstrated gender and age invariance. Article 3 – among a few significant predictors, only age (r = -0.348 and r = -0.341) and vigorous LTPA (r = 0.276 and r = 0.140) were found to be significantly and independently associated with both Preference and Tolerance scores, respectively. In addition, population-based normative values stratified by age categories are presented. Article 4 – controlling for age, gender, BMI and past LTPA levels, a 1-unit increase in Preference and/or Tolerance scores was associated with additional ≈5min/week of total LTPA, ≈2min/week of moderate LTPA and ≈2min/week of vigorous LTPA. In addition, considering the recommended levels of LTPA, a 1-unit increase in Preference and/or Tolerance scores was associated with ≈4-6%, 12.4% and 9.1% greater odds of longitudinally attaining the recommended levels of total, moderate and vigorous LTPA, respectively.